THE ANALYSIS OF TRANSITIVITY PROCESS OF STUDENTS’ DESCRIPTIVE TEXTS - Tia Listiana Apendi; Euis Rina Mulyani (IKIP Siliwangi, 2020)
This research analysis transitivity process of the descriptive text written by the students at seventh grade in junior high school. The objectives of this research is to find out the use of transitivity process of students’ descriptive texts and to find out the most dominant of transitivity process. This reseach analyzed 60 sentences taken from eight descriptive texts written by the students. The researcher used descriptive quantitative method to analyzed the transitivity process. The result of this research showed that there were six processes that occured in the data, there were; material process (41,6%), mental process (1,7%), relational process (38,3%), behavioral process (1,7%), verbal process (1,7%), and existenntial process (15%). The most dominant process found were material process and relational process. It implies that the students were aware how descriptive text should be written, because one of language features in descriptive text is using material process and relational process accordance the definition that descriptive text is describe about person, place, things, or the outward of something like daily activity during the students used simple present tense in each verbs. Keywords: SFL, Transitivity, Descriptive text